2021
DOI: 10.1177/25165984211031687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tool rotation on the fabrication of micro-tool by electrochemical micromachining

Abstract: Electrochemical micromachining (EMM) uses anodic dissolution in the range of microns to remove material. Complex shapes that are difficult to machine on hard materials can be fabricated easily with the help of EMM without any stresses on the workpiece surface and no tool wear. Fabrication of microfeatures on microdevices is a critical issue in modern technologies. For the fabrication of microfeatures, precise micro-tools have to be fabricated. In this present study, EMM milling is used for the fabrication of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Tool cathode plays an important role in improving the machining accuracy of electrochemical milling, a smooth surface is observed for the micro-tool fabricated by rotating the tool inside the workpiece’s hole, as proper flushing of debris particles takes place due to tool rotation. 11 It is mainly composed of an emery coating adhered to a standard-size cylindrical metal rod. When the full-edge electrochemical milling process is performed, the whole tool cathode edge cuts into cemented carbide, as shown in Figure 1.…”
Section: Theory and Numerical Simulationmentioning
confidence: 99%
“…Tool cathode plays an important role in improving the machining accuracy of electrochemical milling, a smooth surface is observed for the micro-tool fabricated by rotating the tool inside the workpiece’s hole, as proper flushing of debris particles takes place due to tool rotation. 11 It is mainly composed of an emery coating adhered to a standard-size cylindrical metal rod. When the full-edge electrochemical milling process is performed, the whole tool cathode edge cuts into cemented carbide, as shown in Figure 1.…”
Section: Theory and Numerical Simulationmentioning
confidence: 99%
“…studied the effect of tool rotation on the fabrication of micro-tool by micro-ECM. 20 They concluded that a better dissolution with less stray current effect is obtained as tool rotation improves flushing of debris particles. Again, the same author (2021) used Multiphysics simulation to study the current density variation in the IEG during the micro-tool fabrication process through micro-ECM.…”
mentioning
confidence: 99%